PERLINDUNGAN HUKUM TERHADAP ANAK YANG MENGALAMI TINDAK PIDANA PENELANTARAN ANAK - Dedek Srikmulia Hati Ndruru (Jurnal Panah Hukum, 2025)
Child neglect, a heinous crime in which the perpetrator shamelessly relinquishes their duty towards an innocent child, refusing to nurture the life they brought into this world. Children who have been forsaken by their caretakers are bestowed with certain entitlements and shielded under the wing of the State. A unique and defining decision was made, labeled as number 141/Pid.Sus/2015/PN. Skt is a place where unfortunate incidents of child neglect unfold. Henceforth, the focal point of this study lies in unraveling and delving into the realm of legal safeguards designed to shield innocent children who are unfortunate victims of heinous acts synonymous with parental negligence. This study employs a unique blend of normative legal research methods, incorporating elements of statutory regulations, case analysis, comparative analysis, and analytical analysis. The collection of secondary data includes primary legal materials, secondary legal materials, and tertiary legal materials, offering a comprehensive exploration of the subject. The approach to data analysis employed is a descriptive qualitative method, where deductions are made to draw comprehensive conclusions. After delving into extensive research and engaging in fruitful conversations, one can confidently deduce that the safeguarding of children facing the appalling deeds of child neglect is unequivocally secured by Law Number 35 of 2014 pertaining to Child Protection. It is imperative to note that not only is the responsibility of vigilance entrusted upon the governing bodies but also upon society and families themselves, ensuring a collective effort in upholding the prevention of child neglect. This can be observed in the intricacies of Article 26 within the realm of Law Number 35 of 2014, an embodiment of Child Protection. Particularly, it is the government that assumes an immensely significant role and burden of responsibility, ensuring the watchful eye and tender care for those children who have sadly fallen through the cracks of neglect. A testament to this diligence lies within the corridors of Article 23, paragraph (2) of the aforementioned law, further amplifying the government's devoted commitment to safeguarding and nurturing these vulnerable souls. The writer puts forward a proposal for various organizations, such as the Social Service, Central Government, Regional Government, and Women's and Children's Service Institutions, to intensify their efforts in combating child neglect. They recommend that these entities implement outreach programs aimed at the community, specifically addressing issues pertaining to abandoned children.